Compliance with IAS Disclosure Requirements by Financial Institutions in Uganda - Sejjaaka, Samuel K. (Informa UK Limited, 2005)
This study examines the extent of compliance by financial institutions (banks, and insurance firms) with IAS issued by the IASB and adopted in 1999 in Uganda. Despite the banking crisis of the 1990s and the drive to attract more foreign direct investment, we find that the extent of disclosure in the financial sector in terms of compliance with IAS is still poor. When we compare the disclosure scores for the two groups, we find that the scores are not significantly different. This indicates that the problem of low compliance is sector wide, and regulators need to improve on the standard of reporting in Uganda in order to improve acceptability of annual reports.